Rakit yang Terombang-Ambing: Ambivalensi Sikap Politik dan Orientasi Ekonomi Orang Cina di Palembang pada Masa Revolusi - Jumhari, Jumhari (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2024)
The revolutionary period was a time of upheaval and uncertainty for economic actors, including the Chinese community that played a dominant role in Indonesia's economy. During this time, the Chinese engaged in business and trade were caught between two competing powers vying for political and economic influence: the Republic of Indonesia's government and the Dutch government attempting to reassert its imperialist control. Their position was fraught with dilemmas, as they had to navigate conflicting political stances and economic interests. Palembang, as a strategically significant region outside Java with transnational economic connections, particularly with Singapore as a trading hub in Southeast Asia, became a key battleground for political and economic struggles impacting the Chinese community. This article aims to depict the various social, political, and economic realities faced by the Chinese in Palembang during this transitional period of power shifts, using a socio-historical approach.